An outbreak of infantile gastroenteritis due to E. coli 0142. Issue 10 (October 1973) - Kennedy, D. H.; Walker, G. H.; Fallon, R. J.; Boyd, J. F.; Gross, R. J.; Rowe, B.
Abstract : Twelve cases of gastroenteritis caused by Escherichia coli 0142K86H6 are described. Ten of these cases were clearly involved in an outbreak of cross infection. The other two cases yielded interesting information on infection with E. coli . 0142. Five cases, two being fatal, required repeated intravenous infusion, and one further infant required parenteral replacement therapy on a single occasion only. Cross infection occurred at the primary site—a ward partitioned into cubicles—despite full barrier nursing techniques. Infection spread also to two other wards, and resulted from transfer of latently infected cases. Illness in several infants was protracted and debilitating because of the relapsing nature of the infection. The pathology of the two fatalities is reported briefly.